Effect of intercritical temperature on the strain hardening of dual-phase bainite/ferrite steel. Issue 14 (21st September 2020) - Nawaz, Bilal; Yang, Zhinan; Zhang, Fucheng; Li, Junkui
Abstract : Medium-carbon dual-phase bainite/ferrite steels with different bainite and carbide volume fractions were prepared via intercritical annealing and austempering. Bainite dominated the microstructure at high intercritical temperatures, and carbides and ferrite phase dominated at low temperatures. Carbides existed in two types, undissolved alloy–cementite and vanadium carbide. The ferrite grain size was reduced to 1.22 ± 0.7 µm at 790°C. Modified Crussard–Jaoul (MC–J) model was used to analyse the strain hardening process, and the highest strain hardening rate was obtained at 755°C. The high carbide fraction at 755°C increased the ferrite dislocation density and enhanced the ferrite phase strength. The high dislocation density in ferrite and the small strength difference in bainite and ferrite enhanced the strain hardening rate at 755°C.